Abstracts book of the Scientific Session of the Faculty of Biology (SSFB), New Trends in Biology: from Molecules to Complex Systems, 4th edition, October 25th - 26th, 2024 - SSFB SSFB (Journal of Experimental and Molecular Biology)
Abstracts of the scientific works that have been presented at the Scientific Session of the Faculty of Biology (SSFB), New Trends in Biology: from Molecules to Complex Systems, 4th edition, October 25-26, 2024, Iasi, Romania